On the differential impact of the Asian crisis on the world economy: a general equilibrium perspective - Diao, Xinshen; Li, Wenli; Yeldan, A. Erinc (Wiley, 2002)
Three years and more have passed since the outbreak of the Asian Financial crisis in 1997. We observe that the world economy was far from a ‘global slump,‘ yet the burden of adjustment had been uneven across countries. The crisis had a negative effect on the other developing countries, while the impact on industrial economies had been small, and even positive at the onset of the crisis. In this paper, we attempt to shed light on this differential impact of the crisis, and illustrate the uneven mechanics of adjustment in a world with commodity trade and capital flows. The analysis is conducted in an intertemporal general equilibrium model with multi‐region and multi‐commodity specification.